PREPAID ENERGY METER USING GSM/GPRS - Mr. Rushikesh J. Admane; Mr. Shubham P. Chavan; Prof. Dhavale A. A. (International Journal of Innovations in Engineering Research and Technology, 2023)
The work carried out here in this paper represents designing and implementing a digital prepaid energy meter which this affordable for domestic consumers in a developing countries. The prepaid energy meter is a single phase 230V/40A energy meter which consist of a metering devise designed according to the IEC1036 (1996-09) standard and a prepaid module that uses GSM/GPRS technology to communicate with the utility server. In this project researchers have proposed prepaid energy meter by using Arduino nano, GSM SIM800L. The main advantage of this work is fast collection of electricity bill, less involvement of human in the process, increased speed of operation. And along with it the work will make the system paperless.